The Effectiveness of Cooperative Learning Models Tai and Stad Type in Improving Student's Critical Thinking - Yhusita Tyas Margaretha; Agustina Tyas Asri Hardini (Green Publisher Indonesia, 2021)
This study aims to determine the level of effectiveness of thecooperative learning model type TAI